Analysis of Teacher Techniques for Teaching Speaking Skills at SMAN 1 IV Koto Aur Malintang - Melani, Yultri; Syafei, An Fauzia Rozani (Universitas Negeri Padang, 2024)
This study aimed to find out the techniques employed by the teacher and how the teacher implements techniques for teaching speaking skills at SMAN 1 IV Koto Aur Malintang. This study was focused on one English teacher as an object of the study. The data in this study were the results of the observation checklist when teaching speaking in the classroom. The observation of this study was conducted to check whether the activities mentioned in the observation checklist are available in the classroom. The result of the analysis showed that the techniques employed by the teacher in teaching speaking at SMAN 1 IV Koto Aur Malintang were brainstorming, discussion, and role-play. Moreover, there are few activities that the teacher passes over crucial aspects in different teaching techniques employed that may impact teaching and they are short time limits, lack of reminders for the next session, lack of attention to the discussion topic, reflection on vocab in the story, and feedback from other groups. The findings suggest the teacher gains a better understanding of the activities associated with the techniques being applied. This knowledge would enable the teacher to take more appropriate actions in the classroom. This can be done by joining the training, seminars or workshops facilitated by the school.